EFFECT OF CHROMIUM PROPIONATE ON THE HUMORAL IMMUNE RESPONSE AND PERFORMANCE OF BROILERS VACCINATED AGAINST NEWCASTLE DISEASE IN THE TROPICS - D. C. Eze; E. C. Okwor; W. U. Anike; H. M. Kazeem; K. A. Majiyagbe (Journal of Animal and Plant Sciences, 2014)
Chromium (Cr) has been considered as an essential micronutrient for humans and animals by nutritionists. The primary role of Cr in metabolism is in enhancing the glucose uptake by the cells. Its supplementation reduces the negative effects of environmental stress. Newcastle Disease (ND) virus potentially infects most species of birds, and for susceptible poultry it is highly contagious and usually fatal. Humoral immune responses indicated that total antibody titers to ND vaccines were much higher in groups I, III, and V chicks that received Chromium Propionate (Cr-Prop) when compared to groups II and IV that did not received Cr-Prop. Humoral immune responses of group I (2.1) was higher than group II (1.9) while that in group III (2.3) was higher than group IV (1.3) and group V had (2.5). Cr-Prop supplementation significantly (p < 0.05) increased body weights of the broilers. The body weight in group I (3.23Kg) was significantly (p < 0.05) higher than those in group II (2.55Kg), while, those in group III (3.13Kg) were higher than those in groups IV (2.62Kg) and V (3.29 Kg). The weekly mean body weight gains of the treated groups I, III and V at the end of the study were significantly (p ≥ 0.05) higher than those of untreated groups II and IV. The feed conversion ratio revealed variable significant (p ≥ 0.05) differences which did not reflect dietary inclusion of organic Cr-Prop. Cr-Prop supplementation improved the immune response to ND vaccine and the performance of broiler such as live body weight, body weight gain, and feed intake and feed conversion ratio in broilers.
Keywords: Chromium propionate·Newcastle disease·Immune response·Broiler performance· Vaccination